2020
DOI: 10.1177/0967391120965115
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermal and dynamic-mechanical studies of functionalized halloysite nanotubes reinforced polypropylene composites

Abstract: Mechanical, dynamic-mechanical and thermal performance of polypropylene (PP) composites which are composed of (3-Aminopropyl) triethoxysilane (APTES) functionalized Halloysite nanotubes (HNTs) were investigated. Functionalization of HNTs was confirmed by the presence of amine stretching peaks in the FTIR spectrum. A decrease in the agglomeration and high dispersion of APTES-HNTs across the PP matrix was confirmed by scanning electron micrographs (SEM). The mechanical properties of APTES-HNT-PP polymer composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Slight variation (2 °C) was registered in T g . 60 Attapulgite (ATP) clay was intercalated with γ-methacryloxypropyl trimethoxysilane (KH-570) and butyl acrylate. The modified matter was added to the PP matrix at different proportions (1 to 7 wt.%).…”
Section: Resultsmentioning
confidence: 99%
“…Slight variation (2 °C) was registered in T g . 60 Attapulgite (ATP) clay was intercalated with γ-methacryloxypropyl trimethoxysilane (KH-570) and butyl acrylate. The modified matter was added to the PP matrix at different proportions (1 to 7 wt.%).…”
Section: Resultsmentioning
confidence: 99%
“…MAPP addition in all composite formulation is based on previous studies in which PP based GNP, GO, and HNTs nanocomposite systems without interfacial modification showed decreased mechanical properties especially, tensile strength and impact strength compared to modified PP nanocomposites. [13,32,37,38] MAPP at 4 phr in all formulations is based on previous studies in which MAPP at 4 phr was found sufficient to enhance dispersion at varying filler contents. [10,39] All materials of formulation were oven dried for 24 h at 100 C to remove adsorbed moisture.…”
Section: Preparation Of Pp Nanocompositesmentioning
confidence: 99%
“…Krishnaiah et al . 20 , 21 adapted the surface of HNTs with 3-aminopropyltriethoxysilane to enrich the surface communication of HNTs with polylactide and polypropylene. Prashantha et al .…”
Section: Introductionmentioning
confidence: 99%